CARIES PREVENTION IN CHILDREN WITH INFECTIOUS MONONUCLEOSIS - S.V. Savchyn; A.R. Kysil (Український стоматологічний альманах, 2024)
Purpose. To evaluate the effectiveness of the developed complex measures for the prevention of dental caries in children with infectious mononucleosis.